2007
DOI: 10.1143/jpsjs.76sa.100
|View full text |Cite
|
Sign up to set email alerts
|

Rich Behaviors of Vanadium Oxides under High Pressure

Abstract: Vanadium oxides exhibit rich behaviors under high-pressure, for examples, the pressure-temperature (P-T) phase diagram of V 2 O 3 as a prototype of Mott-Hubbard model, a "devil's flower" phase diagram of NaV 2 O 5 derived from the ANNNI model, the pressure-induced superconductivity adjacent to charge order in -A 0.33 V 2 O 5 (A = Li, Na, Ag), a rich P-T phase diagram including the spin-gaped phases with devil's staircase type superlattice modulations in -Sr 0.33 V 2 O 5 , etc. These results reveal that various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…The range of phenomena that they exhibit is wide: spin-Peierls transitions, spin gap formation as well as charge and spin ordering. β-A 0.33 V 2 O 5 bronzes (A = Li, Na, Ag) undergo metal-insulator phase transitions with successive charge-spin ordering at atmospheric conditions [6][7][8][9][10][11][12][13][14][15]. They are superconducting below about 9 K at pressures above 7 GPa [6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The range of phenomena that they exhibit is wide: spin-Peierls transitions, spin gap formation as well as charge and spin ordering. β-A 0.33 V 2 O 5 bronzes (A = Li, Na, Ag) undergo metal-insulator phase transitions with successive charge-spin ordering at atmospheric conditions [6][7][8][9][10][11][12][13][14][15]. They are superconducting below about 9 K at pressures above 7 GPa [6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…β-A 0.33 V 2 O 5 bronzes (A = Li, Na, Ag) undergo metal-insulator phase transitions with successive charge-spin ordering at atmospheric conditions [6][7][8][9][10][11][12][13][14][15]. They are superconducting below about 9 K at pressures above 7 GPa [6][7][8][9][10][11][12][13][14]. The exact mechanism of the superconductivity has been debated [7][8][9][10][11][12][13][14] ever since the article by Yamauchi et al has been published [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Recently, it has been reported that Ir incorporation in ZnS:Mn remarkably increases the quantum efficiency of PL. 13 In addition, similar improvements have also been achieved in ZnS:Cu, ZnSe:Mn, and SrS:Ce. 13 Thus, one can expect that this effect also contributes extensively to the improvement of the performance of II-VI-based light-emitting devices such as EL displays.…”
mentioning
confidence: 63%
“…13 In addition, similar improvements have also been achieved in ZnS:Cu, ZnSe:Mn, and SrS:Ce. 13 Thus, one can expect that this effect also contributes extensively to the improvement of the performance of II-VI-based light-emitting devices such as EL displays. On the other hand, the mechanism for this improved PL by Ir incorporation has not been investigated to date.…”
mentioning
confidence: 63%